(untitled) (Global Journal of Human-Social Science, 2019)
This paper on managing the challenges of women and youth empowerment programmes in Nigeria has the following objectives to determine the challenges facing women and youth empowerment programmes in Nigeria and to determine the prospects for youth and women empowerment in Nigeria Mostly secondary data were used in the study Findings reveal that there are so many challenges working against youth and women empowerment in Nigeria namely instability in government policies failed health facilities unplanned strikes Boko Haram and Fulani herdsmen menace kidnapping lack of necessary infrastructure and so on Prospects for women and youth empowerment include but not limited to reduction in the rate of unemployment stability in government policies installation of effective efficient and result oriented economic team profitable negotiation land use law reforms improvement in the provision of quality and well-equipped health facilities and basic infrastructure